Last Cretaceous Geology of Taranaki Basin, New Zealand - Thrasher, Glenn Paul (11658364) (1992)
Taranaki Basin is a large sedimentary basin located along the western side of New Zealand, which contains all of this countries present petroleum production. The basin first formed as the late-Cretaceous Taranaki Rift, and the first widespread sediments are syn-rift deposits associated with this continental rifting. The Taranaki Rift was an obliquely extensional zone which transferred the movement associated with the opening of the New Caledonia Basin southward to the synchronous Tasman Sea oceanic spreading. Along the rift a series of small, en-echelon basins opened, controlled by high-angle normal and strike-slip faults. These small basins presently underlie the much larger Taranaki Basin. Since the initial rift phase, Taranaki Basin has undergone a complex Cenozoic history of subsidence, compression, additional rifting, and minor strike-slip faulting, all usually involving reactivation of the late-Cretaceous rift-controlling faults. One of the late-Cretaceous rift basins is the Pakawau Basin. Rocks deposited in this basin outcrop in Northwest Nelson as the Pakawau Group. Data from the outcrop and from wells drilled in the basin allow the Pakawau Group to be divided into two formations, the Rakopi Formation and the North Cape Formation, each with recognizable members. The Rakopi Formation (new name) is a sequence of terrestrial strata deposited by fans and meandering streams in an enclosed basin. The North Cape Formation is a transgressive sequence of marine, paralic and coastal-plain strata deposited in response to regional flooding of the rift. The coal-measure strata of the Rakopi Formation are organic rich, and are potential petroleum source rocks where buried deeply enough. In contrast, the marine portions of the North Cape Formation contain almost no organic matter and cannot be considered a potential source rock. Sandy facies within both formations have petroleum reservoir potential. The Rakopi and North Cape formations can be correlated with strata intersected by petroleum exploration wells throughout Taranaki Basin, and all syn-rift sediments can be assigned to them. The Taranaki Rift was initiated about 80 Ma, as recorded by the oldest sediments in the Rakopi Formation. The transgression recorded in the North Cape Formation propagated southwards from about 72 to 70 Ma, and the Taranaki Rift remained a large marine embayment until the end of the Cretaceous about 66.5 Ma. Shortly thereafter, a Paleocene regression caused the southern portions of Taranaki Basin to revert to terrestrial (Kapuni Group) sedimentation. The two distinct late Cretaceous sedimentary sequences of the Rakopi and North Cape formations can be identified on seismic reflection data, and the basal trangressive surface that separates them has been mapped throughout the basin. This horizon essentially marks the end of sedimentation in confined, terrestrial subbasins, and the beginning of Taranaki Basin as a single, continental-margin-related basin. Isopach maps show the Rakopi Formation to be up to 3000m thick and confined to fault- controlled basins. The North Cape Formation is up to 1500m thick and was deposited in a large north-south embayment, open to the New Caledonia basin to the northwest. This embayment was predominantly a shallow-marine feature, with shoreline and lower coastal plain facies deposited around its perimeter